Feasibility and tolerability of physiologic monitoring among pregnant nurses and nursing teams - Isha Agarwal; Madeleine Puissant; Irit Altman; Alexandra Hinton; Tania D. Strout; Erika L. Sabbath (Pilot and Feasibility Studies)
Background Most studies of stress during pregnancy have relied on self-reported and recalled measures, leaving a knowledge gap about the impact of acute, or momentary, stressors. Heart rate, blood pressure, and cortisol are physiologic measures known to increase acutely in response to acute stress. The feasibility of collecting these measures has not been widely reported among pregnant workers outside of a controlled laboratory setting. Methods This pilot study assessed the feasibility and tolerability of measuring ambulatory heart rate, blood pressure, and diurnal urine cortisol during periods of work and rest among pregnant nurses, nursing assistants, and clinical technicians. Results Over a 9-month enrollment period, we received 31 inquiries from potential candidates, of whom 18 met our eligibility criteria and 12 accepted enrollment (67% acceptance rate). Over the study period, 4 enrollees withdrew their participation, and 8 were retained until the end of the study (67% completion rate). Our feasibility threshold was the acquisition of ≥ 80% of expected measurements for heart rate, blood pressure, and urine cortisol among retained participants. We achieved our feasibility target for blood pressure recordings (acquiring 84% of expected measures) but not for heart rate recordings (acquiring 60% of expected measures). Urine cortisol levels were successfully obtained 97% of the time. Through qualitative analysis of comments provided by study participants, we identified three major themes surrounding barriers to completing physiological monitoring: (1) personal discomfort and technical issues with study equipment, (2) work or activity interference, and (3) concerns about study design. Conclusions While physiologic monitoring of pregnant workers is important for learning about how work might impact pregnancy outcomes, equipment challenges pose a significant barrier to study participation. Future studies should allow for a significant withdrawal rate or explore alternative equipment options.